PsycEXTRA Dataset 2005
DOI: 10.1037/e633942013-392
|View full text |Cite
|
Sign up to set email alerts
|

Relationship problems and physical aggression: The moderating role of temporal comparison

Abstract: Because physical aggression in relationships frequently occurs within the context of disagreements, partners with more fodder for disagreements (e.g., more relationship problems) may be especially prone to engage in aggression. However, this may be less true among partners who have a means of coping with their relationship problems. Because previous research suggests that perceptions of improvement serve as a coping strategy in a wide range of adverse circumstances, the current study examined whether this copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Most of the research on nonvoluntary dependence has focused on abusive relationships, in which satisfaction may not be directing decisions to remain with a partner (e.g., Bauserman & Arias, 1992; Follingstad, Rogers, & Duvall, 2012; Frye, 2006; Rhatigan & Axsom, 2006; Rusbult & Martz, 1995). However, nonvoluntary dependence, as stated above, is not limited to abusive or aggressive relationships and occurs when people remain committed to their relationship and satisfaction wanes as a determining factor regarding staying in the relationship.…”
Section: Nonvoluntary Dependencementioning
confidence: 99%
“…Most of the research on nonvoluntary dependence has focused on abusive relationships, in which satisfaction may not be directing decisions to remain with a partner (e.g., Bauserman & Arias, 1992; Follingstad, Rogers, & Duvall, 2012; Frye, 2006; Rhatigan & Axsom, 2006; Rusbult & Martz, 1995). However, nonvoluntary dependence, as stated above, is not limited to abusive or aggressive relationships and occurs when people remain committed to their relationship and satisfaction wanes as a determining factor regarding staying in the relationship.…”
Section: Nonvoluntary Dependencementioning
confidence: 99%
“…Both illusory improvement and temporal projection patterns would predict that relationship quality at the time of forecast should increase the tendency to predict more change to the better in global relationship judgments for the future. Indeed, this has been borne out in past research (Baker et al, 2017; Frye, 2006; Lemay, 2016; Rusbult et al, 2001). In a study on temporal comparison, Frye (2006) found that the more satisfied participants reported being in their relationship, the more positive change in relationship problems they expected (although the extent to which this expected change might be illusory could not be determined in this particular study, since actual change was not assessed).…”
Section: Illusory Improvementmentioning
confidence: 87%
“…Indeed, this has been borne out in past research (Baker et al, 2017; Frye, 2006; Lemay, 2016; Rusbult et al, 2001). In a study on temporal comparison, Frye (2006) found that the more satisfied participants reported being in their relationship, the more positive change in relationship problems they expected (although the extent to which this expected change might be illusory could not be determined in this particular study, since actual change was not assessed). In the present studies we examine the link of perceived relationship quality with the extent of bias in predicted future relationship quality (Study 1) and examine whether experimental manipulation of relationship quality at the time of forecast increases the extent of positive forecasting bias (Study 2).…”
Section: Illusory Improvementmentioning
confidence: 87%